The effects of physical activity on human gut microbiota composition: a systematic review. (30th September 2020) - Dorelli, B; Iachini, M; Zaccarin, M; Preziosi Standoli, J; Galle, F; Valeriani, F; Liguori, G; Romano Spica, V; Cattaruzza, M S; De Vito, C
Abstract: Background: Gut microbiota development and composition can be influenced by an existing dynamic balance between host physiology and lifestyle. This systematic review aims to assess the impact of physical activity on human gut microbiota. Methods: PubMed, Scopus and Web of Science were searched until May 2019. Full-text in English were recruited if focused on gut microbiota in healthy athletes or active people, without age or gender restrictions, collected on faecal samples and analysed with genome sequencing of rRNA 16S. All types of study design were included as long as they performed a comparison with a sedentary control group. No specific time frame for the publication date was applied. Quality assessment was performed using the JBI Critical Appraisal Checklist for Analytical Cross Sectional Studies (2017) and Cochrane Risk of Bias Tool for Randomized Controlled Trials. Results: The analysis yielded 7/985 articles: five cross-sectional studies and two clinical trials, published from 2014 to 2019. The overall methodological assessment was of fair quality. Types of exercise included in the studies were: rugby, running, aerobic exercise, bodybuilding. More in detail, regarding the exercise load, some studies were conducted on elite professional athletes, such as rugby players, marathon runners or bodybuilders, with rigorous training, while other studies included a few weeks of aerobic and resistance training at a moderate intensity. Shannon diversity index increased in three studies. Concerning phyla, Firmicutes were increased in five studies and three studies described a significant decrease in Bacteroides. Conclusions: This systematic review confirms the direct correlation between microbiota composition and physical activity, but further studies are needed to establish the possible presence of a causal link between the two factors. Key messages: Exercise can play an important role as an environmental factor in determining gut microbiota composition. Further studies are needed to gain robust evidence of physical activity influence on gut microbiota variability.